2018
DOI: 10.1590/0102-311x00077617
|View full text |Cite
|
Sign up to set email alerts
|

Gradiente urbano-rural no padrão de consumo e cessação do tabagismo no Brasil

Abstract: The degree of urbanization has been associated with both tobacco consumption and quit rates. The current study aims to examine the importance of the urban-rural context in the determination of tobacco consumption patterns and smoking cessation. Data were used from the supplement of the Special Survey on Smoking (PETab) from the 2008 Brazilian National Household Sample Survey (PNAD). The sample included 14,420 individuals over 15 years of age, of whom 7,003 were current smokers and 7,417 former smokers in the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
1
0
3
Order By: Relevance
“…Ultimately, rural area residents have easy access to illicit cigarettes and have less access to and less impact on information to raise awareness of the effects of tobacco [ 39 ]. In turn, the association between smoking and living in an urban area found in this study can be explained by high urbanization, which has been strongly associated with greater commercialization of tobacco products, aggressive marketing by producing companies, and an unfavorable regulatory environment in several urban areas [ 40 ]. Additionally, adolescents and young people in urban areas have higher incomes and education, social determinants significantly associated with access to and use of tobacco products [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, rural area residents have easy access to illicit cigarettes and have less access to and less impact on information to raise awareness of the effects of tobacco [ 39 ]. In turn, the association between smoking and living in an urban area found in this study can be explained by high urbanization, which has been strongly associated with greater commercialization of tobacco products, aggressive marketing by producing companies, and an unfavorable regulatory environment in several urban areas [ 40 ]. Additionally, adolescents and young people in urban areas have higher incomes and education, social determinants significantly associated with access to and use of tobacco products [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study with older people in southern Brazil found similar percentages of elderly smokers living in the rural (13%) and urban areas (14%) [23]. On the other hand, a Brazilian study, which evaluated the importance of the urban-rural context in determining the pattern of consumption of tobacco products, illustrated that, despite the knowledge that the degree of urbanization was associated with the consumption of tobacco products, the places least influenced by the urban environment had a higher prevalence of smoking and smoking cessation was higher in the more urbanized places [24].…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, assim como no restante do mundo, o uso do tabaco varia segundo diferentes características demográficas e socioeconômicas. Evidências empíricas para o contexto brasileiro indicam, por exemplo, que o tabagismo é mais frequente entre homens, negros, jovens, solteiros e divorciados, aqueles com menor escolaridade e renda e moradores de áreas rurais (Bazotti et al 2016;Kuhnen et al 2009;Muzi et al 2018).…”
Section: Consumo De Tabaco No Brasilunclassified